Tests of self-compacting concrete filled elliptical steel tube columns. (January 2017) - Mahgub, M.; Ashour, A.; Lam, D.; Dai, X.
Abstract: This paper presents an experimental study into the axial compressive behaviour of self-compacting concrete filled elliptical steel tube columns. In total, ten specimens, including two empty columns, with various lengths, section sizes and concrete strengths were tested to failure. The experimental results indicated that the failure modes of the self-compacting concrete filled elliptical steel tube columns with large slenderness ratio were dominated by global buckling. Furthermore, the composite columns possessed higher critical axial compressive capacities compared with their hollow section companions due to the composite interaction. However, due to the large slenderness ratio of the test specimens, the change of compressive strength of concrete core did not show significant effect on the critical axial compressive capacity of concrete filled columns although the axial compressive capacity increased with the concrete grade increase. The comparison between the axial compressive load capacities obtained from experimental study and prediction using simple methods provided in Eurocode 4 for concrete-filled steel circular tube columns showed a reasonable agreement. The experimental results, analysis and comparison presented in this paper clearly support the application of self-compacting concrete filled elliptical steel tube columns in construction engineering practice. Highlights: This manuscript represents test results of eight elliptical tube columns filled with SCC and two empty columns. The main cause of failure for all the columns tested was a global buckling. The EC4 method showed reliable results for all columns tested. The European buckling curves for steel columns can be considered as the basis of elliptical CFT column design. The axial compressive load capacity of composite columns increases with an increase in SCC compressive strength.